2007
DOI: 10.1111/j.1502-3931.2007.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the ultrastructure, permeability, and integrity of conodont apatite determined by transmission electron microscopy

Abstract: 2007: New insights into the ultrastructure, permeability, and integrity of conodont apatite determined by transmission electron microscopy. Lethaia , Vol. 40, New crystalline structures have been observed in argon ion-milled conodont elements from a diverse suite of Ordovician taxa (' Cordylodus robustus ', Drepanoistodus suberectus , Panderodus gracilis , Plectodina ? sp., Aphelognathus sp., Periodon aculeatus ), using transmission electron microscopy (TEM). Electron diffraction patterns of albid tissue revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…2E) has discussed the errors of Donoghue's (1998) interpretation of conodont morphogenesis providing clear morphogenetic diagrams for vertebrate odontodes and showing how the structure and growth of conodont elements does not match the Odontode Regulation Th eory (Reif 2002) in any way. As noted above, Trotter et al (2007) also showed that conodont element tissues are clearly distinct in crystal size from any vertebrate tissue. Th ere is also no mineralized keratin in conodont elements, and so affi nities with rasping teeth of lampreys and hagfi shes are also very unlikely.…”
Section: Skeletal Elementsmentioning
confidence: 61%
See 4 more Smart Citations
“…2E) has discussed the errors of Donoghue's (1998) interpretation of conodont morphogenesis providing clear morphogenetic diagrams for vertebrate odontodes and showing how the structure and growth of conodont elements does not match the Odontode Regulation Th eory (Reif 2002) in any way. As noted above, Trotter et al (2007) also showed that conodont element tissues are clearly distinct in crystal size from any vertebrate tissue. Th ere is also no mineralized keratin in conodont elements, and so affi nities with rasping teeth of lampreys and hagfi shes are also very unlikely.…”
Section: Skeletal Elementsmentioning
confidence: 61%
“…Donoghue et al (2000Donoghue et al ( , 2006 considered conodont basal bodies to be formed of dentine, but the globular tissue they discuss cannot be homologous with vertebrate dentine, which grows centripetally (Gross 1954(Gross , 1957Schultze 1996;Reif 2006;Fig. 2E), and is added basally not topically (Trotter et al 2007). Even just considering the basal body structure, Carter & Lutz (1990: pl.…”
Section: Dentinementioning
confidence: 99%
See 3 more Smart Citations